Gregory the Great : Perfection in Imperfection. - Straw, Carole (Transformation of the Classical Heritage, 14., 1991)
Gregory I (590-604) is often considered the first medieval pope and the first exponent of a truly medieval spirituality. Carole Straw places Gregory in his historical context and considers the many facets of his personalitymonk, preacher, and popein order to elucidate the structure of his thought and present a unified, thematic interpretation of his spiritual concerns.